High-performance copper-nickel-tin alloy and preparation process thereof

By adding lanthanum and yttrium to copper-nickel tin alloys and a specific preparation process, the problem of insufficient performance of traditional copper-nickel tin alloys is solved, and the preparation of high-performance copper-nickel tin alloys is realized, meeting the needs of modern industry.

CN119530611AInactive Publication Date: 2025-02-28国工恒昌新材料(义乌)有限公司

Patent Information

Application Number
CN202510073405.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional copper-nickel-tin alloys have shortcomings in performance and are difficult to meet the needs of modern industry, especially high-end manufacturing and cutting-edge technologies.

Method used

The composition and structure of the alloy are optimized by adding a specific proportion of lanthanum and yttrium as rare earth elements to the copper nickel-tin alloy, combined with specific preparation process steps such as vacuum induction smelting, refining, casting, homogenization treatment, hot rolling, cold rolling and aging treatment.

Benefits of technology

It significantly improves the tensile strength, yield strength, elongation and hardness of copper-nickel-tin alloys, while improving the conductivity, meeting the needs of high-performance metal materials in modern industry.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-performance copper-nickel-tin alloy and a preparation process thereof, and relates to the technical field of alloy materials, and the high-performance copper-nickel-tin alloy comprises the following components in percentage by weight: 10%-14% of nickel, 4%-7% of tin, 0.2%-0.5% of beryllium, 0.6%-1.6% of iron, 0.4%-0.7% of zinc, 0.06%-0.22% of magnesium, 0.01%-0.04% of phosphorus, 0.07%-0.14% of rare earth element X and the balance of copper and inevitable impurities. The preparation process comprises the following steps: smelting: putting raw materials into a vacuum induction smelting furnace, vacuumizing to 0.003-0.008 Pa, filling argon until the pressure in the furnace is 0.03-0.04 MPa, gradually heating to 1200-1260 DEG C according to the heating rate of 11-15 DEG C / min, and keeping the temperature for 30-50 minutes to obtain an alloy melt; under the combined action of all the components, the mechanical property parameters of the copper-nickel-tin alloy are remarkably improved, and after rare earth elements lanthanum and yttrium are added, the tensile strength, the yield strength, the ductility and the hardness of the copper-nickel-tin alloy are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy materials, in particular to a high-performance copper-nickel-tin alloy and a preparation process thereof. Background Art

[0002] Copper-nickel-tin alloy is an important copper-based alloy. As an important engineering material, copper-nickel-tin alloy is widely used in many fields such as aerospace, electronics, and machinery manufacturing. It is based on copper and adds elements such as nickel and tin. This alloy combines the good electrical conductivity and thermal conductivity of copper with the strengthening effect brought by nickel and tin. It plays a key role in many industrial fields and is widely used in aerospace, aviation, shipbuilding, electronics, electrical engineering, machinery, chemical industry, electroplating and other industries.

[0003] In many fields of modern industry, such as electronics, electrical, aerospace, and high-end equipment manufacturing, the demand for high-performance metal materials continues to grow and the requirements are becoming increasingly stringent. Copper-nickel-tin alloy has certain comprehensive properties. Traditional copper-nickel-tin alloy still has many shortcomings in performance and is difficult to meet the needs of today's cutting-edge technology and high-end manufacturing. Therefore, it is of great significance to develop a copper-nickel-tin alloy with better comprehensive performance and its preparation process. To this end, a high-performance copper-nickel-tin alloy and its preparation process are provided to solve the above problems. Summary of the invention

[0004] The object of the present invention is to provide a high-performance copper-nickel-tin alloy and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions: A high-performance copper-nickel-tin alloy comprises the following components by weight percentage: nickel: 10-14%, tin: 4-7%, beryllium: 0.2-0.5%, iron: 0.6-1.6%, zinc: 0.4-0.7%, magnesium: 0.06-0.22%, phosphorus: 0.01-0.04%, rare earth element X: 0.07-0.14%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the weight ratio of lanthanum to yttrium is 3:1-5:2.

[0006] As an improved solution of the present invention: a high-performance copper-nickel-tin alloy comprises the following components by weight percentage: nickel: 10-13%, tin: 5-7%, beryllium: 0.2-0.4%, iron: 0.7-1.5%, zinc: 0.4-0.6%, magnesium: 0.07-0.2%, phosphorus: 0.01-0.03%, rare earth element X: 0.08-0.13%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the weight ratio of lanthanum to yttrium is 3:1.1-5:2.

[0007] As an improved solution of the present invention: a high-performance copper-nickel-tin alloy, calculated by weight percentage, includes the following components: nickel: 12%, tin: 6%, beryllium: 0.3%, iron: 1.2%, zinc: 0.5%, magnesium: 0.16%, phosphorus: 0.02%, rare earth element X: 0.11%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the weight ratio of lanthanum to yttrium is 8:3.

[0008] The preparation process of high performance copper-nickel-tin alloy includes the following steps: (1) Ingredients: Weigh electrolytic copper, nickel blocks, tin particles, beryllium blocks, iron powder, zinc particles, magnesium bars, phosphorus powder and rare earth metal blocks with a purity of not less than 99.5% according to the alloy composition ratio; (2) Melting: Place the raw materials in a vacuum induction melting furnace, evacuate to 0.003-0.008Pa, fill with argon until the pressure in the furnace is 0.03-0.04MPa, gradually heat to 1200-1260℃ at a heating rate of 11-15℃ / min, and keep warm for 30-50min to obtain an alloy melt; (3) Refining: At 1200-1260°C, high-purity argon gas at a flow rate of 8-12 L / min is introduced into the furnace for refining for 10-12 minutes; (4) Casting: The alloy melt is cast into a metal mold preheated to 320-350°C to form an ingot; (5) Homogenization treatment: The ingot is homogenized at 800-850°C for 4-6 hours, first cooled to 550-600°C in the furnace, and then air-cooled to room temperature; (6) Hot rolling: hot rolling the ingot at 680-750°C, with a total hot rolling deformation of 55-65%, and a final rolling temperature of not less than 550°C; (7) Cold rolling: The hot-rolled plate is cold rolled, with a total cold rolling deformation of 35-45%. One or two stress relief annealings are performed in the middle, with an annealing temperature of 420-450°C and an annealing time of 1-1.5 hours each time. (8) Aging treatment: The cold-rolled sheet is placed in an aging furnace for aging treatment at 450-500°C for 3-4 hours, and then air-cooled to room temperature.

[0009] As an improved solution of the present invention: in the smelting step of the preparation process of the high-performance copper-nickel-tin alloy, beryllium and phosphorus are added in the form of an intermediate alloy.

[0010] As an improved solution of the present invention: in the refining step of the preparation process of the high-performance copper-nickel-tin alloy, the purity of the high-purity argon gas is not less than 99.95%.

[0011] As an improved solution of the present invention: in the homogenization step of the preparation process of the high-performance copper-nickel-tin alloy, the furnace cooling rate is 12-18°C / min.

[0012] As an improved solution of the present invention: in the hot rolling step of the preparation process of the high-performance copper-nickel-tin alloy, the reduction rate during the hot rolling process is 0.6-1.2 mm / s.

[0013] As an improved solution of the present invention: in the aging treatment step of the preparation process of the high-performance copper-nickel-tin alloy, the atmosphere in the aging furnace is a mixed gas of argon and hydrogen, wherein the volume fraction of hydrogen is 1-3%.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention significantly improves the mechanical performance parameters of the copper-nickel-tin alloy under the joint action of various components. After adding the rare earth elements lanthanum and yttrium, the tensile strength, yield strength, elongation and hardness of the copper-nickel-tin alloy are significantly improved. The addition of rare earth elements during the preparation of the copper-nickel-tin alloy improves the crystal structure of the alloy, reduces the obstacles to electron conduction such as lattice defects, and makes the movement of electrons in the alloy smoother, thereby significantly improving the electrical conductivity of the copper-nickel-tin alloy. DETAILED DESCRIPTION

[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention: Example 1

[0016] In the embodiment of the present invention, the high-performance copper-nickel-tin alloy includes the following components by weight percentage: nickel: 10%, tin: 4%, beryllium: 0.2%, iron: 0.6%, zinc: 0.4%, magnesium: 0.06%, phosphorus: 0.01%, rare earth element X: 0.07%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the ratio of lanthanum to yttrium by weight is 3:1.

[0017] The preparation process of high performance copper-nickel-tin alloy comprises the following steps: (1) Ingredients: Weigh electrolytic copper, nickel blocks, tin particles, beryllium blocks, iron powder, zinc particles, magnesium bars, phosphorus powder and rare earth metal blocks with a purity of not less than 99.5% according to the alloy composition ratio; (2) Melting: Place the raw materials in a vacuum induction melting furnace, evacuate to 0.003 Pa, fill with argon until the pressure in the furnace is 0.03 MPa, gradually heat up to 1200°C at a heating rate of 11°C / min, and keep warm for 30 minutes to obtain an alloy melt. During the melting step, beryllium and phosphorus are added in the form of an intermediate alloy.

[0018] (3) Refining: At 1200°C, high-purity argon gas at a flow rate of 8 L / min is introduced into the furnace for refining for 10 minutes. The purity of the high-purity argon gas is not less than 99.95%.

[0019] (4) Casting: The alloy melt is cast into a metal mold preheated to 320°C to form an ingot; (5) Homogenization treatment: The ingot was homogenized at 800°C for 4 hours, first cooled to 550°C in the furnace, and then air-cooled to room temperature. During the homogenization step, the cooling rate was 12°C / min. (6) Hot rolling: The ingot is hot rolled at 680°C, the total deformation of the hot rolling is 55%, the final rolling temperature is not less than 550°C, and the reduction rate during the hot rolling process is 0.6 mm / s (7) Cold rolling: The hot-rolled plate is cold rolled, with a total cold rolling deformation of 35%. A stress relief annealing is performed in the middle, the annealing temperature is 420°C, and each annealing time is 1 hour; (8) Aging treatment: The cold-rolled sheet is placed in an aging furnace for aging treatment at 450°C for 3 hours, and then air-cooled to room temperature. During the aging treatment step, the atmosphere in the aging furnace is a mixed gas of argon and hydrogen, in which the volume fraction of hydrogen is 1%. Example 2

[0020] In the embodiment of the present invention, the high-performance copper-nickel-tin alloy includes the following components by weight percentage: nickel: 14%, tin: 7%, beryllium: 0.5%, iron: 1.6%, zinc: 0.7%, magnesium: 0.22%, phosphorus: 0.04%, rare earth element X: 0.14%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the ratio of lanthanum to yttrium by weight is 5:2.

[0021] The preparation process of high performance copper-nickel-tin alloy comprises the following steps: (1) Ingredients: Weigh electrolytic copper, nickel blocks, tin particles, beryllium blocks, iron powder, zinc particles, magnesium bars, phosphorus powder and rare earth metal blocks with a purity of not less than 99.5% according to the alloy composition ratio; (2) Melting: Place the raw materials in a vacuum induction melting furnace, evacuate to 0.008 Pa, fill with argon until the pressure in the furnace is 0.04 MPa, gradually heat to 1260°C at a heating rate of 15°C / min, and keep warm for 50 minutes to obtain an alloy melt. During the melting step, beryllium and phosphorus are added in the form of an intermediate alloy.

[0022] (3) Refining: At 1260°C, high-purity argon gas at a flow rate of 12 L / min is introduced into the furnace for refining for 12 minutes. During the refining step, the purity of the high-purity argon gas is not less than 99.95%.

[0023] (4) Casting: The alloy melt is cast into a metal mold preheated to 350°C to form an ingot.

[0024] (5) Homogenization treatment: The ingot was homogenized at 850 °C for 6 h, first cooled to 600 °C in the furnace and then air-cooled to room temperature. During the homogenization step, the cooling rate was 18 °C / min.

[0025] (6) Hot rolling: the ingot is hot rolled at 680-750°C, the total deformation of the hot rolling is 65%, the final rolling temperature is not less than 550°C, and the reduction rate during the hot rolling process is 1.2 mm / s.

[0026] (7) Cold rolling: The hot-rolled plate is cold rolled, with a total cold rolling deformation of 45%. Two stress relief annealings are performed in the middle, with an annealing temperature of 450°C and an annealing time of 1.5 hours each time; (8) Aging treatment: The cold-rolled sheet is placed in an aging furnace for aging treatment at 500°C for 4 hours, and then air-cooled to room temperature. During the aging treatment step, the atmosphere in the aging furnace is a mixed gas of argon and hydrogen, in which the volume fraction of hydrogen is 3%. Example 3

[0027] In the embodiment of the present invention, the high-performance copper-nickel-tin alloy includes the following components by weight percentage: nickel: 10%, tin: 5%, beryllium: 0.2%, iron: 0.7, zinc: 0.4%, magnesium: 0.07%, phosphorus: 0.01%, rare earth element X: 0.08%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the weight ratio of lanthanum to yttrium is 3:1.1.

[0028] The preparation process of high performance copper-nickel-tin alloy comprises the following steps: (1) Ingredients: Weigh electrolytic copper, nickel blocks, tin particles, beryllium blocks, iron powder, zinc particles, magnesium bars, phosphorus powder and rare earth metal blocks with a purity of not less than 99.5% according to the alloy composition ratio; (2) Melting: Place the raw materials in a vacuum induction melting furnace, evacuate to 0.005 Pa, fill with argon until the pressure in the furnace is 0.035 MPa, gradually heat to 1240°C at a heating rate of 12°C / min, and keep warm for 40 minutes to obtain an alloy melt. During the melting step, beryllium and phosphorus are added in the form of an intermediate alloy.

[0029] (3) Refining: At 1240°C, high-purity argon gas at a flow rate of 9 L / min is introduced into the furnace for refining for 11 minutes. During the refining step, the purity of the high-purity argon gas is not less than 99.95%.

[0030] (4) Casting: Casting the alloy melt into a metal mold preheated to 330°C to form an ingot; (5) Homogenization treatment: The ingot was homogenized at 830°C for 5 hours, first cooled to 580°C in the furnace and then air-cooled to room temperature. During the homogenization step, the cooling rate was 15°C / min.

[0031] (6) Hot rolling: the ingot is hot rolled at 720°C, the total deformation of the hot rolling is 62%, the final rolling temperature is not less than 550°C, and the reduction rate during the hot rolling process is 0.9 mm / s.

[0032] (7) Cold rolling: The hot-rolled plate is cold rolled, with a total cold rolling deformation of 42%. Stress relief annealing is performed 1.5 times in the middle, with an annealing temperature of 430°C and an annealing time of 1.2 hours each time; (8) Aging treatment: The cold-rolled sheet is placed in an aging furnace for aging treatment at 480°C for 3-4 hours, and then air-cooled to room temperature. During the aging treatment step, the atmosphere in the aging furnace is a mixed gas of argon and hydrogen, in which the volume fraction of hydrogen is 2%. Example 4

[0033] In the embodiment of the present invention, the high-performance copper-nickel-tin alloy includes the following components by weight percentage: nickel: 13%, tin: 7%, beryllium: 0.4%, iron: 1.5%, zinc: 0.6%, magnesium: 0.2%, phosphorus: 0.03%, rare earth element X: 0.13%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the ratio of lanthanum to yttrium by weight is 5:2.

[0034] The preparation process of high performance copper-nickel-tin alloy comprises the following steps: (1) Ingredients: Weigh electrolytic copper, nickel blocks, tin particles, beryllium blocks, iron powder, zinc particles, magnesium bars, phosphorus powder and rare earth metal blocks with a purity of not less than 99.5% according to the alloy composition ratio; (2) Melting: Place the raw materials in a vacuum induction melting furnace, evacuate to 0.005 Pa, fill with argon until the pressure in the furnace is 0.035 MPa, gradually heat to 1240°C at a heating rate of 12°C / min, and keep warm for 40 minutes to obtain an alloy melt. During the melting step, beryllium and phosphorus are added in the form of an intermediate alloy.

[0035] (3) Refining: At 1240°C, high-purity argon gas at a flow rate of 9 L / min is introduced into the furnace for refining for 11 minutes. During the refining step, the purity of the high-purity argon gas is not less than 99.95%.

[0036] (4) Casting: Casting the alloy melt into a metal mold preheated to 330°C to form an ingot; (5) Homogenization treatment: The ingot was homogenized at 830°C for 5 hours, first cooled to 580°C in the furnace and then air-cooled to room temperature. During the homogenization step, the cooling rate was 15°C / min.

[0037] (6) Hot rolling: the ingot is hot rolled at 720°C, the total deformation of the hot rolling is 62%, the final rolling temperature is not less than 550°C, and the reduction rate during the hot rolling process is 0.9 mm / s.

[0038] (7) Cold rolling: The hot-rolled plate is cold rolled, with a total cold rolling deformation of 42%. Stress relief annealing is performed 1.5 times in the middle, with an annealing temperature of 430°C and an annealing time of 1.2 hours each time; (8) Aging treatment: The cold-rolled sheet is placed in an aging furnace for aging treatment at 480°C for 3-4 hours, and then air-cooled to room temperature. During the aging treatment step, the atmosphere in the aging furnace is a mixed gas of argon and hydrogen, in which the volume fraction of hydrogen is 2%. Example 5

[0039] In the embodiment of the present invention, the high-performance copper-nickel-tin alloy includes the following components by weight percentage: nickel: 12%, tin: 6%, beryllium: 0.3%, iron: 1.2%, zinc: 0.5%, magnesium: 0.16%, phosphorus: 0.02%, rare earth element X: 0.11%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the ratio of lanthanum to yttrium by weight is 8:3.

[0040] The preparation process of high performance copper-nickel-tin alloy comprises the following steps: (1) Ingredients: Weigh electrolytic copper, nickel blocks, tin particles, beryllium blocks, iron powder, zinc particles, magnesium bars, phosphorus powder and rare earth metal blocks with a purity of not less than 99.5% according to the alloy composition ratio; (2) Melting: Place the raw materials in a vacuum induction melting furnace, evacuate to 0.005 Pa, fill with argon until the pressure in the furnace is 0.035 MPa, gradually heat to 1240°C at a heating rate of 12°C / min, and keep warm for 40 minutes to obtain an alloy melt. During the melting step, beryllium and phosphorus are added in the form of an intermediate alloy.

[0041] (3) Refining: At 1240°C, high-purity argon gas at a flow rate of 9 L / min is introduced into the furnace for refining for 11 minutes. During the refining step, the purity of the high-purity argon gas is not less than 99.95%.

[0042] (4) Casting: Casting the alloy melt into a metal mold preheated to 330°C to form an ingot; (5) Homogenization treatment: The ingot was homogenized at 830°C for 5 hours, first cooled to 580°C in the furnace and then air-cooled to room temperature. During the homogenization step, the cooling rate was 15°C / min.

[0043] (6) Hot rolling: the ingot is hot rolled at 720°C, the total deformation of the hot rolling is 62%, the final rolling temperature is not less than 550°C, and the reduction rate during the hot rolling process is 0.9 mm / s.

[0044] (7) Cold rolling: The hot-rolled plate is cold rolled, with a total cold rolling deformation of 42%. Stress relief annealing is performed 1.5 times in the middle, with an annealing temperature of 430°C and an annealing time of 1.2 hours each time; (8) Aging treatment: The cold-rolled sheet is placed in an aging furnace for aging treatment at 480°C for 3-4 hours, and then air-cooled to room temperature. During the aging treatment step, the atmosphere in the aging furnace is a mixed gas of argon and hydrogen, in which the volume fraction of hydrogen is 2%.

[0045] Comparative Example 1 Except for not containing rare earth element X, other components and preparation process steps are consistent with those of Example 5.

[0046] The high performance copper-nickel-tin alloys prepared in Examples 1-5 and Comparative Example 1 were tested for alloy properties, and the results are shown in Table 1: Table 1 Group Tensile strength (MPa) Yield strength (MPa) Elongation (%) Hardness (HV) Conductivity (%IACS) Example 1 830 504 9 176 10.2 Example 2 907 521 10 184 12.1 Example 3 942 543 11 201 13.2 Example 4 961 550 8 223 15.3 Example 5 1022 597 15 265 18.4 Comparative Example 1 703 443 7 162 9.6 From the above data, it can be concluded that the present invention improves the tensile strength and yield strength of the copper-nickel-tin alloy under the joint action of each component: it can be seen from the data of the embodiments and comparative examples that after adding the rare earth element X, the tensile strength and yield strength of the alloy are significantly improved. In Example 5, the tensile strength of the copper-nickel-tin alloy reaches 1022MPa, and the yield strength reaches 597MPa, while the tensile strength of the copper-nickel-tin alloy without the rare earth element X in Comparative Example 1 is only 703MPa, and the yield strength is 443MPa. The addition of rare earth elements X (lanthanum and yttrium) can refine the alloy grains. During the solidification process of the alloy, the rare earth elements act as heterogeneous nuclei, which increase the nucleation rate of grain growth, thereby refining the grains. The fine grain strengthening effect enables the grain boundaries to effectively hinder the movement of dislocations when the alloy is subjected to force, thereby improving the strength of the material.

[0047] At the same time, the elongation of the copper-nickel-tin alloy is also increased. In Example 5, the elongation of the copper-nickel-tin alloy is 15%, and that of Comparative Example 1 is 7%. The addition of the rare earth element X improves the organizational structure of the alloy, so that the alloy can better coordinate deformation during the stretching process, reduce stress concentration, and thus improve the plastic deformation capacity of the material. In addition, the hot rolling, cold rolling, and aging treatment processes in the preparation process work together with the rare earth elements to optimize the organizational structure inside the alloy, so that the alloy has improved elongation while maintaining a high strength.

[0048] In addition, in terms of hardness, the hardness of the copper-nickel-tin alloy obtained by adding rare earth element X is significantly higher than that of the alloy without rare earth element. The hardness of Example 5 is 265HV, and that of Comparative Example 1 is 162HV. Due to the combined effect of rare earth element grain refinement and strengthening phase formed with other alloy elements, grain refinement strengthening and dispersion strengthening (second phase particles formed by rare earth elements and other elements are dispersed in the matrix) enhance the ability of the alloy to resist local deformation, thereby improving the hardness.

[0049] In terms of conductivity, from the conductivity data, in Example 5, the conductivity of the copper-nickel-tin alloy is 18.4% IACS, and that of the comparative example 1 is 9.6% IACS. The addition of the rare earth element X improves the crystal structure of the copper-nickel-tin alloy, reduces the obstacles to electron conduction such as lattice defects, and makes the movement of electrons in the alloy smoother, thereby improving the conductivity.

Claims

1. A high performance copper-nickel-tin alloy, characterized in that: The invention comprises the following components by weight percentage: nickel: 10-14%, tin: 4-7%, beryllium: 0.2-0.5%, iron: 0.6-1.6%, zinc: 0.4-0.7%, magnesium: 0.06-0.22%, phosphorus: 0.01-0.04%, rare earth element X: 0.07-0.14%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the weight ratio of lanthanum to yttrium is 3:1-5:

2.

2. The high performance copper-nickel-tin alloy according to claim 1, characterized in that: The invention comprises the following components by weight percentage: nickel: 10-13%, tin: 5-7%, beryllium: 0.2-0.4%, iron: 0.7-1.5%, zinc: 0.4-0.6%, magnesium: 0.07-0.2%, phosphorus: 0.01-0.03%, rare earth element X: 0.08-0.13%, and the rest is copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the weight ratio of lanthanum to yttrium is 3:1.1-5:

2.

3. The high performance copper-nickel-tin alloy according to claim 1, characterized in that: By weight percentage, it includes the following components: Nickel: 12%, tin: 6%, beryllium: 0.3%, iron: 1.2%, zinc: 0.5%, magnesium: 0.16%, phosphorus: 0.02%, rare earth element X: 0.11%, and the rest are copper and unavoidable impurities, wherein the rare earth element X is a mixture of lanthanum and yttrium, and the ratio of lanthanum to yttrium by weight is 8:

3.

4. The preparation process of the high performance copper-nickel-tin alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Ingredients: Weigh electrolytic copper, nickel blocks, tin particles, beryllium blocks, iron powder, zinc particles, magnesium bars, phosphorus powder and rare earth metal blocks with a purity of not less than 99.5% according to the alloy composition ratio; (2) Melting: Place the raw materials in a vacuum induction melting furnace, evacuate to 0.003-0.008Pa, fill with argon until the pressure in the furnace is 0.03-0.04MPa, gradually heat to 1200-1260℃ at a heating rate of 11-15℃ / min, and keep warm for 30-50min to obtain an alloy melt; (3) Refining: At 1200-1260°C, high-purity argon gas at a flow rate of 8-12 L / min is introduced into the furnace for refining for 10-12 minutes; (4) Casting: The alloy melt is cast into a metal mold preheated to 320-350°C to form an ingot; (5) Homogenization treatment: The ingot is homogenized at 800-850°C for 4-6 hours, first cooled to 550-600°C in the furnace, and then air-cooled to room temperature; (6) Hot rolling: The ingot is hot rolled at 680-750°C, the total deformation of hot rolling is 55-65%, and the final rolling temperature is not less than 550°C; (7) Cold rolling: The hot-rolled plate is cold rolled, with a total cold rolling deformation of 35-45%. One or two stress relief annealings are performed in the middle, with an annealing temperature of 420-450°C and an annealing time of 1-1.5 hours each time. (8) Aging treatment: The cold-rolled sheet is placed in an aging furnace for aging treatment at 450-500°C for 3-4 hours, and then air-cooled to room temperature.

5. The preparation process according to claim 4, characterized in that: During the smelting step, beryllium and phosphorus are added in the form of a master alloy.

6. The preparation process according to claim 4, characterized in that: In the refining step, the purity of the high-purity argon gas is not less than 99.95%.

7. The preparation process according to claim 4, characterized in that: During the homogenization step, the furnace cooling rate was 12-18°C / min.

8. The preparation process according to claim 4, characterized in that: In the hot rolling step, the reduction rate during hot rolling is 0.6-1.2 mm / s.

9. The preparation process according to claim 4, characterized in that: In the aging treatment step, the atmosphere in the aging furnace is a mixed gas of argon and hydrogen, wherein the volume fraction of hydrogen is 1-3%.

Citation Information

Patent Citations

  • High strength elastic brass and preparation method thereof

    CN103421980A

  • Multi-stage combination deformation heat treatment method for ultrahigh-strength CuNiSn-series elastic copper alloy

    CN108060325A

  • Reduction preparation method of copper-based elastic alloy thin strip

    CN108453222A

  • Cu-15Ni-8Sn copper alloy, copper alloy bar and preparing method of copper alloy bar

    CN108677059A

  • Wear-resistant copper-nickel-tin alloy and preparation method thereof

    CN113278846A

Cited By

  • High-conductivity wear-resistant copper alloy and preparation method and application thereof

    CN120174231A